Nanotermometria óptica com nanocristais dopados com os íons ativos Tm+3 e Ho3+ - Pereira, Alexsandro de Farias (2016)
In this work, we investigated the luminescence properties of sodium niobate (NaNbO3) and lanthanum fluoride (LaF3) nanoparticles (NPs) doped or co-doped with different rare-earth ions for potential applications in photonic devices, in particular bio-image, optical nanoheater, and luminescence nanothermometers (LNTs) operating within and without of regions known as first and second biological windows (I-BW and II-BW, respectively). Firstly, we investigate the potential applications of Tm3+/Yb3+ codoped NaNbO3 NPs as high-resolution LNT under three-photon excitation. For this, we analyzed the behavior of the fluorescence intensity ratio (FIR) at 480 and 486 nm (which comprise the luminescence band around 480 nm) in the temperature range of 24 to 140 ° C. It was observed that the FIR shows a linear behavior with temperature and, from these data, it was possible to estimate the thermal sensitivity of the LNT. Next, we investigated the potential of the NPs to convert light into heat, where it was possible to measure the optically induced local temperature on the NPs´ surface. Upconversion emission at 800 nm (3H4 → 3H6) under two-photon excitation of NaNbO3 NPs doped with different Tm3+ concentrations (1-5 mol%) was investigated for potential applications as LNT operating within BWs and in fluorescent bio-imaging. To this, we investigate, respectively, the luminescence spectral profile around 800 nm in the temperature range of 22-90 ° C and the penetration depth of the laser excitation at 1319 nm. We also investigated the potential applications of NIR fluorescence of LaF3 NPs doped with different Tm3+ concentrations (1, 3 and 5 mol%) and high sensitivity LNT operating with emission in the II-BW and excitement in the I-BW. To this end, the FIR at 1470 nm (3H4 → 3F4) and 1230 nm (3H5 → 3H6) were analyzed in the temperature range of 24 to 88 oC. By end, we studied the potential application as LNT (with excitation and emission within the BWs) the Yb3+/Ho3+ codoped LaF3 NPs based on the emission profile around 1188 nm of Ho3+ ions. In summary, the present thesis had as primary focus the study of LNTs operating in biological tissues transparent regions and in the blue region of the electromagnetic spectrum.